2017
DOI: 10.1016/s1470-2045(17)30155-9
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation-based classification and grading system for meningioma: a multicentre, retrospective analysis

Abstract: Link to publication record in Explore Bristol Research PDF-document This is the author accepted manuscript (AAM). The final published version (version of record) is available online via Lancet at https://www.sciencedirect.com/science/article/pii/S1470204517301559?via%3Dihub . Please refer to any applicable terms of use of the publisher. University of Bristol -Explore Bristol Research General rightsThis document is made available in accordance with publisher policies. Please cite only the published version usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

27
676
3
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 646 publications
(716 citation statements)
references
References 48 publications
27
676
3
10
Order By: Relevance
“…A number of mutations as well as DNA methylation profiles have all been shown to be linked with the risk of recurrence in meningioma. [58, 59] Addition of molecular markers has the potential to significantly improve not only understanding of the biology of meningioma, but refine prognostic and treatment stratification as well as development of more targeted treatment modalities. Importantly, this study has demonstrated that early recurrence/progression of atypical meningioma was significantly related to neurological outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…A number of mutations as well as DNA methylation profiles have all been shown to be linked with the risk of recurrence in meningioma. [58, 59] Addition of molecular markers has the potential to significantly improve not only understanding of the biology of meningioma, but refine prognostic and treatment stratification as well as development of more targeted treatment modalities. Importantly, this study has demonstrated that early recurrence/progression of atypical meningioma was significantly related to neurological outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…This hypomethylation, frequently seen early in cancer development, is commonly followed by locus-specific hypermethylation. Large-scale analyses have shown that DNA methylation aberrations are frequently present in cancers [9] and that DNA methylation profiling enables distinguishing cancer subtypes [10] and classifying cancers of unknown primary origin [11].A variety of DNA methylation aberrations have been suggested as biomarkers for early detection, prognostication and monitoring of cancer, including in noninvasive clinical material such as blood, stool, urine and bile. Great hopes are also tied to DNA methylation as a direct target for epigenetic therapy.…”
mentioning
confidence: 99%
“…This hypomethylation, frequently seen early in cancer development, is commonly followed by locus-specific hypermethylation. Large-scale analyses have shown that DNA methylation aberrations are frequently present in cancers [9] and that DNA methylation profiling enables distinguishing cancer subtypes [10] and classifying cancers of unknown primary origin [11].…”
mentioning
confidence: 99%
“…Following surgical resection, the designation of a WHO histological grade provides prognostic information and determines a potential indication for adjuvant therapy. Reassuringly, 80% of meningiomas show benign clinical behaviour and can be cured with resection alone, particularly those in favourable accessible locations 7. Benign WHO Grade I meningiomas have a five year overall survival of over 80%, and after a complete resection, the 10 year recurrence for grade I meningiomas varies from 20% to 39% 9…”
Section: Discussionmentioning
confidence: 99%